Implementation Of Regional Regulation Of The Province Of East Java No. 1 Of 2018 Concerning The Zonation Plan Of Coastal Areas And Small Islands (Zpcasi) In Sumenep Regency, East Java - I Dewa Ayu Tya Saraswati,Bambang Satriya, Supriyadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In implementing the regional regulation of East Java province number 1 of 2018 concerning the Zoning Plan for Coastal Areas and Small Islands (ZPCASI), of course there are many things that need to be studied and carried out a more in-depth study, so the purpose of this study is to describe and analyze the implementation of the regulations. East Java province number 1 of 2018 concerning ZPCASI. In addition, the purpose of this study is to formulate strategic plans and recommendations to minimize deviations in the implementation of these regional regulations. The method used is to use normative law research methods using normative studies in the form of legal behavior products such as reviewing laws. The results of this study can be concluded that the implementation of East Java Province Regulation No. 1 of 2018 concerning ZPCASI is a joint effort for the formation of policies and development of coastal areas and small islands which are carried out by implementing the prevailing laws and regulations. According to the researcher, the law that regulates the environment provides a more structured space for the community and managers of policy interests in managing coastal areas. In addition, the management of coastal areas and small islands is carried out by the government, policy makers and the community as well as stakeholders in the implementation of the Regional Regulation of East Java Province No. 1 of 2018 concerning ZPCASI is also seen by the efforts to form local regulations to the grassroots level by referring to local regulations and laws. In addition, the strategies and recommendations carried out in the implementation of the East Java Provincial Regulation No. 1 of 2018 concerning ZPCASI, namely by strengthening provincial regulations by making derivative regulations in districts. After that, the strengthening of public knowledge and awareness was carried out through socialization and introduction of provincial and derivative perda to policy makers.